2013
DOI: 10.3386/w19375
|View full text |Cite
|
Sign up to set email alerts
|

Tail Risk and Asset Prices

Abstract: We propose a new measure of time-varying tail risk that is directly estimable from the cross section of returns. We exploit firm-level price crashes every month to identify common fluctuations in tail risk across stocks. Our tail measure is significantly correlated with tail risk measures extracted from S&P 500 index options, but is available for a longer sample since it is calculated from equity data. We show that tail risk has strong predictive power for aggregate market returns: A one standard deviation inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(112 citation statements)
references
References 26 publications
3
108
1
Order By: Relevance
“…A number of recent studies have suggested that aggregate U.S. stock market return is predictable over horizons ranging up to a few quarters based on the difference between optionsimplied and actual realized variation measures, or the so-called variance risk premium (see, e.g., Bollerslev, Tauchen, and Zhou, 2009;Drechsler and Yaron, 2011;Gabaix, 2011;Kelly, 2011;Zhou, 2010;Zhou and Zhu, 2009, among others). These findings of apparent predictability over relatively short quarterly horizons have potentially far reaching implications for many issues in asset pricing finance.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies have suggested that aggregate U.S. stock market return is predictable over horizons ranging up to a few quarters based on the difference between optionsimplied and actual realized variation measures, or the so-called variance risk premium (see, e.g., Bollerslev, Tauchen, and Zhou, 2009;Drechsler and Yaron, 2011;Gabaix, 2011;Kelly, 2011;Zhou, 2010;Zhou and Zhu, 2009, among others). These findings of apparent predictability over relatively short quarterly horizons have potentially far reaching implications for many issues in asset pricing finance.…”
Section: Introductionmentioning
confidence: 99%
“…Starting with Rietz (), researchers have modeled the possibility of rare disasters, such as economic depressions or wars, to resolve the equity premium puzzle and related puzzles (e.g., Barro () and Gabaix (, )). Kelly () uses firm‐level stock price crashes every month to identify common fluctuations in tail risk across stocks and finds that past tail risk predicts future returns in the cross‐section. The disasters in the rare disasters literature are similar to the jumps we are interested in, but there are some differences: disasters are extremely rare and they do not match well the short‐dated options that we use in constructing the JUMP and VOL factors.…”
mentioning
confidence: 99%
“…A growing number of articles have used the market return variance, skewness, and kurtosis to predict and explain the cross-section of returns (Bali and Murray (2013), Bali, Cakici, and Whitelaw (2011), Chang, Christoffersen, and Jacobs (2013), and Amaya, Christoffersen, Jacobs, and Vasquez (2015)). Kelly and Jiang (2014) show that tail risk has strong predictive power for aggregate market returns and also explain the cross-section of returns. Bollerslev and Todorov (2011) and Bollerslev, Todorov, and Xu (2015) show how information extracted from options can be used to forecast future market return.…”
Section: Theoretical Motivation For Using Sdf Moments In Asset Pricingmentioning
confidence: 94%